HARMONIZATION OF TAX LEGISLATION OF THE ASEAN COMMUNITY - TANAPONG DAMKERNGKHAJORNWONG (Universitas Bengkulu, 2016)
Abstract This article indicates how tax legislations, both in direct and indirect fields, of ASEAN countries should be harmonized. With respect to direct taxation, the issue of direct tax rates harmonization - personal income tax and corporate income tax - will firstly be discussed. Further, I will look into how the personal income tax treatment on a resident exercising the free movement of skilled labour should be. In addition, how to enhance the network of tax treaties between ASEAN Member States and withholding tax levied on cross-border transaction will also be described. As regards indirect taxation, I will consider to what extent such the consumption tax systems as VAT and GST in each ASEAN countries could be in accordance with each other. Finally, what challenges over tax harmonization in ASEAN can be will be noted. The majority of the discussions above will be based upon the tax harmonization and coordination already conducted within the EU.